The intersection between menopause and depression: overview of research using animal models - Herrera-Pérez, José Jaime; Hernández-Hernández, Olivia Tania; Flores-Ramos, Mónica; Cueto-Escobedo, Jonathan; Rodríguez-Landa, Juan Francisco; Martínez-Mota, Lucía (Frontiers in Psychiatry, 2024)
Menopausal women may experience symptoms of depression, sometimes even progressing clinical depression requiring treatment to improve quality of life. While varying levels of estrogen in perimenopause may contribute to an increased biological vulnerability to mood disturbances, the effectiveness of estrogen replacement therapy (ERT) in the relief of depressive symptoms remains controversial. Menopausal depression has a complex, multifactorial etiology, that has limited the identification of optimal treatment strategies for the management of this psychiatric complaint. Nevertheless, clinical evidence increasingly supports the notion that estrogen exerts neuroprotective effects on brain structures related to mood regulation. Indeed, research using preclinical animal models continues to improve our understanding of menopause and the effectiveness of ERT and other substances at treating depression-like behaviors. However, questions regarding the efficacy of ERT in perimenopause have been raised. These questions may be answered by further investigation using specific animal models of reduced ovarian function. This review compares and discusses the advantages and pitfalls of different models emulating the menopausal stages and their relationship with the onset of depressive-like signs, as well as the efficacy and mechanisms of conventional and novel ERTs in treating depressive-like behavior. Ovariectomized young rats, middle-to-old aged intact rats, and females treated with reprotoxics have all been used as models of menopause, with stages ranging from surgical menopause to perimenopause. Additionally, this manuscript discusses the impact of organistic and therapeutic variables that may improve or reduce the antidepressant response of females to ERT. Findings from these models have revealed the complexity of the dynamic changes occurring in brain function during menopausal transition, reinforcing the idea that the best approach is timely intervention considering the opportunity window, in addition to the careful selection of treatment according to the presence or absence of reproductive tissue. Additionally, data from animal models has yielded evidence to support new promising estrogens that could be considered as ERTs with antidepressant properties and actions in endocrine situations in which traditional ERTs are not effective.